Testing the Waters: Applying Marketing Channels Research in Chinese Elevator Industry - Wang, Weihua; Wang, Deli; Wang, Jingjing; Ma, Guoxin; Hong, Mengjiao (INTI International University, 2020)
This paper sets off on the intersection of two fronts. First, there is a long-established literature on marketing channels literature. Second, the Chinese elevator industry has been booming in light of China's rapid developments in the past three decades. Yet, rarely has there been discussion regarding how marketing channels literature can be applied to the elevator industry especially in the Chinese context. We argue that elevator industry in China has remained very conventional in terms of marketing efforts which may impose significant barriers to its further expansion, and accordingly tests the waters by trying to apply marketing channels research in Chinese elevator industry. We provide overviews of the Chinese elevator industry and the literature development of marketing channels in both Western and Chinese contexts, finishing with a preliminary discussion of how the literature could apply in the context of the elevator industry in China.